Plastic changes induced by muscle focal vibration: A possible mechanism for long-term motor improvements - Filippi, Guido M.; Rodio, Angelo; Fattorini, Luigi; Faralli, Mario; Ricci, Giampietro; Pettorossi, Vito E. (Frontiers in Neuroscience, 2023)
Repetitive focal vibrations can induce positive and persistent after-effects. There is still no satisfactory interpretation of the underlying mechanisms. A rationale, which can provide consistency among different results, is highly desirable to guide both the use of the application and future research. To date, interpretive models are formulated to justify the results, depending on the specific protocol adopted. Indeed, protocol parameters, such as stimulus intensity and frequency, intervention time and administration period, are variable among different studies. However, in this article, we have identified features of the protocols that may allow us to suggest a possible common mechanism underlying the effectiveness of focal vibration under different physiologic and pathologic conditions. Since repetitive focal muscle vibration induces powerful and prolonged activation of muscle proprioceptors, we hypothesize that this intense activation generates adaptive synaptic changes along sensory and motor circuits. This may lead to long-term synaptic potentiation in the central network, inducing an enhancement of the learning capability. The plastic event could increase proprioceptive discriminative ability and accuracy of the spatial reference frame and, consequently, improve motor planning and execution for different motor functions and in the presence of different motor dysfunctions. The proposed mechanism may explain the surprising and sometimes particularly rapid improvements in motor execution in healthy and diseased individuals, regardless of specific physical training. This hypothetic mechanism may require experimental evidence and could lead to extend and adapt the application of the "learning without training" paradigms to other functional and recovery needs.